Extraction of Total Triterpenoid Saponins from Ganoderma lucidum by Box-Behnken Design - He, Liang; Gong, Xingguo; Cheng, Junwen; Wu, Xueqian; Wu, Qingqi; Li, Haibo (Asian Journal of Chemistry, 2011)
A three-factor, three-level Box-Behnken factorial design combined with response surface methodology was conducted to optimize ultrasonic-assisted extraction for triterpenoid-enriched extract from Ganoderma lucidum. Three independent variables were extraction time (X1), ultrasonic power (X2) and ratio of solution to solid (X3), respectively. The experimental data obtained were fitted to a second-order polynomial equation with analysis of multiple regressions. The results demonstrated that those three factors significantly affected the yield of total triterpenoid saponins (TPS) from Ganoderma lucidum. The optimal processing conditions of the extraction of total triterpenoid saponins by ultrasound treatment were determined: extraction time 27 min, ultrasonic power 135 w and ratio of solution to solid 47 mL/g. At this condition, the actual yield of total triterpenoid saponins was 1.122 %, which increased by a factor of 1.35 compared with that of classical extraction. Scanning electron microscopic (SEM) images of the fungal cells after ultrasound treatment were obtained to provide visual evidence of the disruption effect.